Reaching Global Marine Biodiversity Conservation Goals With Area-Based Fisheries Management: A Typology-Based Evaluation - Amber Himes-Cornell; Juan Francisco Lechuga Sánchez; Caroline Potter; Clayton McKean; Jake Rice; Kim J. Friedman; Serge M. Garcia; Dave L. Fluharty (Frontiers in Marine Science, 2022)
In 2010, the Parties to the Convention on Biological Diversity (CBD) adopted the Aichi Biodiversity Target 11, calling for conserving 10% of the ocean through marine protected areas (MPAs) and “ other effective area-based conservation measures ” (OECMs), explicitly recognizing that other types of spatial conservation measures beyond areas designated as MPAs may also achieve biodiversity gains. Eight years later, CBD Parties adopted a definition and criteria for OECMs, and by early 2022, only a few OECMs had been reported. The OECM definition clearly requires that the measures be area-based and likely to contribute to conservation. However, conservation need not be their primary objective. Guidance on the extent and limits of what these “area measures” might include is needed. Clarity would assist countries in delivering on the CBD’s Post-2020 Global Biodiversity Framework, with decadal goals incorporating an area-based conservation target, in which OECMs will play a crucial role. To achieve greater recognition of OECMs, countries require sector-specific guidance to guide recognition, listing, and ongoing implementation of OECMs. Here, we evaluate how well area-based fisheries management measures meet the OECM criteria as well as sustainable use principles, broader ecosystem management objectives, and more general biodiversity conservation goals. We systematically review case studies across a broad range of spatial management approaches to provide evidence of correspondence with the OECM criteria, arguing that many with primary objectives related to fisheries sustainability provide co-benefits for biodiversity, and hence biodiversity conservation and sustainable development. This review highlights how fisheries measures can help achieve a number of Sustainable Development Goals alongside the global targets for biodiversity of CBD.